Self‐tunable chaotic true random bit generator in current‐mode CMOS circuit with nonlinear distortion analysis. (25th November 2019) - Addabbo, Tommaso; Fort, Ada; Mugnaini, Marco; Petra, Nicola; Takaloo, Hadis; Vignoli, Valerio
Summary: We discuss the low‐complexity integrated circuit design of a true random bit generator with parametric self‐tuning capabilities. The design targets a mixed‐signal complementary metal‐oxide‐semiconductor (CMOS) current‐mode circuit implementing the Sawtooth chaotic map. Starting from the analysis of the proposed circuit topologies, we investigate how the dynamical system behavior is affected by nonlinear distortions, discussing theoretical simplified models and resorting to qualified numerical simulations. The circuit solutions proposed in this paper and validated with experiments represent an improvement of the designs published in literature, proposing technical solutions to solve stability issues and introducing parametric adjustment capabilities while maintaining a strong link with the studied theoretical models. Abstract : We discuss the design of a low‐complexity chaos‐based true random bit generator with parametric self‐tuning capabilities, targeting a mixed‐signal CMOS current‐mode integrated circuit. We investigate how the dynamical system behavior is affected by nonlinear distortions, discussing theoretical simplified models and resorting to qualified numerical simulations. The investigated solutions represent an improvement of the designs published in literature, proposing technical solutions to solve stability issues, introducing parametric adjustment capabilities, and maintaining a strong link with the studied theoretical models.